Full Proposal 2017-2022 for Phase II of the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) - CGIAR Research Program on Climate Change, Agriculture and Food Security (2016)
Full proposal for the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) for Phase II (2017-2022), revised and submitted to the CGIAR consortium on 29 July 2016. The content and structure of the future program have been developed using the comments of the CGIAR Independent Science and Partnership Council (ISPC), the Joint Consortium Board/Centers/Fund Council Working Group and external partners. A full set of supporting Annexes is included, covering areas such as partnerships, gender, Intellectual Assets, Open Access and Data Management, Results Based Management, Communications, and more.